Meiotic analysis of a cross between cultivated sunflower (Helianthus annuus L. var. macrocarpus) and wild sunflower (Helianthus annuus L. ssp. texanus Heiser) - Rodríguez de la Paz, Jesús; Gómez Martínez, Martha; Reyes Valdés, M. Humberto (Instituto de Ecología, A.C., 2007)
Patterns of meiotic chromosome pairing were compared between three sunflower plants: cultivated sunflower (Helianthus annuus L. var. macrocarpus, public line HA 89), wild sunflower (Helianthus annuus L. ssp. texanus Heiser, collected in Saltillo, Coah.), and the F1 hybrid. The study was carried out through analysis of meiocytes in diakinesis and metaphase I, based on the meiotic configuration frequency. Pollen viability was evaluated by means of a staining method. Chromosome pairing was normal in the three materials, with absence of univalents and multivalents, and only chain and ring bivalents were observed, therefore the parental genomes are highly compatible in meiosis. The hybrid showed a chromosome pairing index of 0.82, close to the midparent value (0.80), and the differences between the hybrid and each parental taxon (cultivated 0.87, and wild 0.75) were highly significant. Besides, this index was variable within populations. This indicates that the chiasma number is under multigenic control and is affected by the environment. Thus, a population formed with both progenitors could be used to analyze the quantitative trait loci (QTLs) for meiotic chromosome pairing. The pollen viability in the hybrid (92.58%) was similar to that found in the parental taxa (wild 95.57%, and cultivated 95.33%). The pollen viability of the F1 was high, it showed fertility, and the parental genomes were highly compatible in meiosis, confirming that there is no barrier for the sexual reproduction, and that gene flow and transference of desirables characters from wild to cultivated H. annuus are easily attainable.